An empirical assessment of the nexus between competition policy and Global Value Chains - Asmaa Ezzat; Chahir Zaki (Research Network Sustainable Global Supply Chains, 2025)
Efficient institutions matter in promoting Global Value Chains (GVCs) participation since they help reduce transaction costs for firms that engage in trade. Competition policy is considered an important dimension of these institutions. This paper investigates whether competition policy matters for participation of emerging countries in GVCs, with a special focus on African countries. To do so, we use the EORA dataset on backward and forward linkages and merge it with different indicators pertaining to the de jure (competition law) and the de facto (market dominance, antimonopoly, etc.) measures of competition policy. We find that both the de jure and the de facto dimensions of competition policy matter for backward and forward GVC participation. In addition, our findings indicate that this relationship is non-linear as the market can become saturated. Two important transmissions channels can explain this effect: market diversification and trade liberalization. These results remain robust after we control for the endogeneity between GVC and competition. In the case of African countries, we find that more diversified economies benefit from competitive markets, whereas other results remain unchanged, especially for the de jure measures.
Keywords: D40; F12; F14; 330; competition policy; GVC; Africa